Magnetic particles for triggering insulin release in INS-1E cells subjected to a rotating magnetic field. Issue 36 (3rd September 2022) - Ponomareva, Svetlana; Joisten, Helene; François, Taina; Naud, Cecile; Morel, Robert; Hou, Yanxia; Myers, Thomas; Joumard, Isabelle; Dieny, Bernard; Carriere, Marie
Abstract : A novel tool for inducing insulin secretion from pancreatic cells. Abstract : Diabetes is a major global health threat. Both academics and industry are striving to develop effective treatments for this disease. In this work, we present a new approach to induce insulin release from β-islet pancreatic cells (INS-1E) by mechanical stimulation. Two types of experiments were carried out. First, a local stimulation was performed by dispersing anisotropic magnetic particles within the cell medium, which settled down almost immediately on cell plasma membranes. Application of a low frequency magnetic field (up to 40 Hz) generated by a custom-made magnetic device resulted in oscillations of these particles, which then exerted a mechanical constraint on the cell plasma membranes. The second type of experiment consisted of a global stimulation, where cells were grown on magneto-elastic membranes composed of a biocompatible polymer with embedded magnetic particles. Upon application of a rotating magnetic field, magnetic particles within the membrane were attracted towards the field source, resulting in the membrane's vibrations being transmitted to the cells grown on it. In both experiments, the cell response to these mechanical stimulations caused by application of the variable magnetic field was quantified via the measurement of insulin release in the growth medium. We demonstrated that the mechanical action induced by the motion of magnetic particles or by membrane vibrations was an efficient stimulus for insulin granule secretion from β-cells. This opens a wide range of possible applications including the design of a system which triggers insulin secretion by β-islet pancreatic cells on demand.